2015
DOI: 10.1111/nan.12187
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Decoding the pathophysiological mechanisms that underlieRNAdysregulation in neurodegenerative disorders: a review of the current state of the art

Abstract: Altered RNA metabolism is a key pathophysiological component causing several neurodegenerative diseases. Genetic mutations causing neurodegeneration occur in coding and noncoding regions of seemingly unrelated genes whose products do not always contribute to the gene expression process. Several pathogenic mechanisms may coexist within a single neuronal cell, including RNA/protein toxic gain-of-function and/or protein loss-of-function. Genetic mutations that cause neurodegenerative disorders disrupt healthy gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 252 publications
(363 reference statements)
1
36
0
2
Order By: Relevance
“…The presence of C9orf72 RNA inclusions in tissues from ALS or frontotemporal dementia (FTD) patients, as well as the formation of similar inclusions in cellular systems expressing the repeats, including iPSC-derived motor neurons, provided an early support for the hypothesis that sequestration of RNA-binding proteins by C9orf72 repeat might have a role in disease pathogenesis (Walsh et al, 2015). Evidence from histopathological analysis of RNA foci in tissues from ALS and/or FTD patients has shown a positive correlation between the number of repeat-containing foci and disease presentation or severity (Cooper-Knock et al, 2014;Mizielinska et al, 2013), further indicating that accumulation of C9orf72-derived G4C2 RNA repeats are primary involved in the neurodegenerative process.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of C9orf72 RNA inclusions in tissues from ALS or frontotemporal dementia (FTD) patients, as well as the formation of similar inclusions in cellular systems expressing the repeats, including iPSC-derived motor neurons, provided an early support for the hypothesis that sequestration of RNA-binding proteins by C9orf72 repeat might have a role in disease pathogenesis (Walsh et al, 2015). Evidence from histopathological analysis of RNA foci in tissues from ALS and/or FTD patients has shown a positive correlation between the number of repeat-containing foci and disease presentation or severity (Cooper-Knock et al, 2014;Mizielinska et al, 2013), further indicating that accumulation of C9orf72-derived G4C2 RNA repeats are primary involved in the neurodegenerative process.…”
Section: Discussionmentioning
confidence: 93%
“…During the past years, the discovery of mutations in the FUS (also known as TLS), TARDBP and C9orf72 genes led to the concept that alterations in RNA metabolism are a major determinant of motor neuron degeneration in amyotrophic lateral sclerosis (ALS), similar to what occurs in other neurodegenerative diseases (Walsh et al, 2015). Alterations in alternative splicing have been suggested to cause the disease, but other steps of posttranscriptional gene regulation could be equally involved (Achsel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mutations affecting TDP-43 and FUS are uncommon in patients with ALS and co-occurring frontotemporal dementia that have higher BMI compared with patients without cognitive symptoms (33,34). The most commonly mutated gene in ALS known to date is chromosome 9 open reading frame 72 (C9ORF72), which encodes a protein of still uncharacterized function (35). Nevertheless, C9ORF72 repeat expansions in a mouse model were associated with TDP-43 pathology, decreased body weight, and hyperactivity (36).…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence for dysregulation of miRNAs in this disease [77]. In 2013 it was reported that endogenous miRNA-155 is significantly upregulated in the spinal cord tissue of both ALS rodent models and human ALS patients [78,79]. In this study, specific ASOs designed to decrease the levels of miRNA-155 in SOD1-G93A mice prolonged survival in this murine model in comparison to scrambled control antimiRNA [78].…”
Section: Dysregulation Of Rna Processing Is Emerging As a Major Pathomentioning
confidence: 83%